Teachers adopting artists' pedagogies: Is it really that simple?. (1st September 2017) - Selkrig, Mark
Bringing artists into learning sites such as schools has resulted in diverse educational benefits for students. As a consequence a gaze has turned to the pedagogies artists employ, to consider how their strategies might inform the practice of 'mainstream' school teachers. With this scrutiny of artists' pedagogies, the voices of artists involved in this type of work and how they describe what they do has received limited attention. Drawing on data from a research project in Australia, which explored the learning for artists who work in educational settings, I consider the teaching approaches these artists described along with 'effective pedagogy' espoused in educational discourse. While acknowledging the good work artists claim they do in educational settings, rather than viewing artist pedagogies as better or competing with teachers' pedagogies, they are or can be complementary. Both art teachers and artists play important roles in school art programmes.